Krajobraz. Próba ujęcia w perspektywie interdyscyplinarnej - Frydryczak, Beata (Studia Europaea Gnesnensia, 2011)
The main purpose of the article is to try and locate the meeting points, but also the substantial discrepancies developed in the course of history, the aesthetics which devises its own notion of landscape and the empirical sciences, humanist geography in particular, which resorts to a broader understanding, incorporating it into the notion of environment. By drawing upon the Renaissance idea of landscape, I point to three factors: landscape painting along with the perspective, theatre and the development of cartography, which significantly contributed to the evolution of an aesthetic notion of landscape. The environmental aesthetics may however play a conciliatory role between the traditional, aesthetic presentation and the standpoint of humanist geography, if one takes into account the assumptions of the latter in terms of shaping the renewed cultural notion of landscape.